Registration of 'FourOsix' Hard Red Winter Wheat. Issue 3 (1st September 2019) - Berg, J. E.; Eberly, J. O.; Lamb, P. F.; Miller, J. H.; Chen, C.; Kephart, K. D.; Pradhan, G. P.; Stougaard, R. N.; Nash, D. L.; Holen, D. L.; Cook, J. P.; Gale, S.; et al.
Abstract : 'FourOsix' (Reg. no. CV‐1153, PI 689753) hard red winter wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in 2018. FourOsix was derived from a composite of five single crosses of the predominant cultivar Yellowstone to advanced Montana breeding lines. FourOsix was developed using a modified bulk breeding method and selected as an F5:6 headrow. FourOsix was tested under the experimental number MT1465 in Montana yield trials from 2014 to 2018. FourOsix is a high‐yielding, winter‐hardy hard red winter wheat cultivar with medium maturity, medium to high grain protein concentration, and excellent milling and baking quality. FourOsix was released for its excellent grain yield performance in winter wheat production environments of Montana, with earlier heading date, reduced plant height, improved grain volume weight, and improved stripe rust resistance relative to Yellowstone.